Comparative Study of the Theoretical Predictions of Mixed-Gas Adsorption Equilibria from Pure Component Adsorption Data: Vacancy Solution Theory - K. Nieszporek (Adsorption Science & Technology)
Simple methods for describing mixed-gas adsorption equilibria based on a knowledge of single gas adsorption are still needed for gas separation processes. The present paper describes the possibilities of the Vacancy Solution Theory (VST) approach. The VST predictions are compared with results obtained using the IAS, IE and PT approaches as presented earlier by the author.